The influence of hemodialysis on intracranial pressure waveform in patients with chronic kidney disease: an observational study - Koch, Mariana Schechtel; Drewnowski, Bianca; Rickli, Cristiane; Santos, Fábio André dos; Baroni, Gilberto; Vellosa, José Carlos Rebuglio (São Paulo Medical Journal, 2025)
BACKGROUND: Among the complications related to chronic kidney disease (CKD), those of a neurological nature stand out, and for a better quality of life for patients, the diagnosis and treatment of these complications is fundamental. OBJECTIVES: This study aimed to assess the effect of hemodialysis on intracranial pressure waveform (ICPw) in patients with chronic kidney disease undergoing hemodialysis and those who are not yet undergoing substitutive therapy. DESIGN AND SETTING: An observational study was conducted in two stages at a kidney replacement therapy center in Brazil. The first was a longitudinal study and the second was a cross-sectional study. METHODS: Forty-two patients on hemodialysis were included in the first stage of the study. In the second stage, 226 participants were included. Of these, 186 were individuals with chronic kidney disease (who were not undergoing substitutive therapy), and 40 did not have the disease (control group). The participants’ intracranial compliance was assessed using the non-invasive Brain4care method, and the results were compared between the groups. RESULTS: There was a significant difference between the hemodialysis and non-hemodialysis groups, with the former having better ICPw conditions. CONCLUSIONS: Hemodialysis influenced the improvement in ICPw, probably due to the decrease in the patients’ extra-and intracellular volumes. Furthermore, ICPw monitoring can be a new parameter to consider when defining the moment to start substitutive therapy.